The Risk of Bag-Carrying Related to Musculoskeletal Pain in Medical Students - R. Ayu Aisyah Hanifah; Indri Seta Septadina; Ramadhan Ananditia Putra (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: Musculoskeletal discomfort affects medical students' neck, shoulders, and back. Musculoskeletal pain may be linked to bag-carrying behaviors, which encompass the manner of carrying, duration of use, and weight of the bag. AIMS:  This study aims to determine the relationship between bag-carrying habits and musculoskeletal pain. METHOD: This is an observational analytic study with a cross-sectional approach. From 2022-2023, the research subjects were 70 Sriwijaya University medical students who met the inclusion and exclusion criteria. The sampling method employed a simple random sampling technique. We analyzed the obtained data using the Chi-square test in SPSS software. RESULT:  The majority of the subject was 20 years old and female. Most patients with musculoskeletal pain experience mild complaints in the lower neck (47.14%), right shoulder (41.43%), and back (41.43%). All of the p-values are> 0,05, including how to carry a bag, bag weight, and the duration of using a bag with neck, shoulder, and back pain among medical students of Sriwijaya University. CONCLUSION: There is no significant relationship between bag-carrying habits, which include how to carry a bag, bag weight, and the duration of using a bag, with neck, shoulder, and back pain among medical students of Sriwijaya University.